Cash Waqf Management for Education: Challenges, Solutions and Strategies - Muhammad Ash- Shiddiqy; Makhrus Makhrus; Muhammad Ghafur Wibowo (Shirkah: Journal of Economics and Business, 2024)
In Indonesia, the potential for funding educational initiatives through the empowerment of cash waqf is considerable, with estimates reaching up to IDR 120 trillion annually. As of March 2022, cash waqf collections amounted to IDR 1.4 trillion, a notable increase from the IDR 855 billion accumulated between 2018 and 2021. Despite this growth, cash waqf collections remain far below their potential, limiting their impact on educational empowerment. While various researchers have proposed strategies to address these obstacles, there is a paucity of research on an ideal model for empowering education through cash waqf in Indonesia. This study aims to develop a model for the empowerment of cash waqf specifically for educational programs in Indonesia. The research utilizes the Analytic Network Process (ANP) methodology, aided by Super Decision software, which is a decision-making method based on priority scales. The study conducts a synthesis analysis of problems, solutions, and strategies related to this issue. The findings indicate that both internal and external challenges affect the empowerment of cash waqf in education, with management being the primary concern. Relevant strategies include waqf policy enhancement, nazhir (waqf managers) training and empowerment, strengthening educational programs, and promoting cash waqf. An investment-based model, coupled with partnerships, scholarships, and educational initiatives, offers insights into the management of cash waqf, from collection processes to empowerment within the educational sector.